Análise dos fatores que influenciam o desempenho dos gestores de relacionamento em agências bancárias de varejo - Dienstmann, Gustavo Henrique (Universidade do Vale do Rio dos Sinos, 2013)
This study was conducted in one of the world´s highest competitive market, which is the banking sector. More specifically aimed to examine ways to increase the performance of retail banking units, which constitute the largest volume of business in this sector. Factors were listed, based in the literature, and investigate the influence on profitability, reduction of nonpayment and attitudinal performance of relationship managers in the retail banking. The constructs analyzed were: conflicts of interest, use of empowerment, concessions, reduced complexity, conservatism, relationship, got it right the first time and competence, and migration to automated services. A Survey was conducted with 291 relationship´s managers dedicating to serving micro and small business in one of the three largest financial institutions in Brazil. The findings revealed a representative relation of "got it right the first time and competence", "relationship" and "conservatism" with increased performance attitudinal. "Got it right the first time and competence," and "relationship" were also related to the reduction of non-payments. "Concessions" also showed negative relation with non-payment. The other constructs analyzed (conflicts of interest, use of empowerment, reducing complexity and migration to automated services) showed no relation with performance. The present study was conducted in a mixed company. Further studies are needed to see if the same results occur in other financial institutions.
Keywords: Bancos varejo; Desempenho; Inadimplência; Fatores; Relacionamento; Fazer certo a primeira vez; Competência; Retail bank; Performance; Non-payment; Concessions; Conservadorism; Relationship; Competence; Got it right the first time; ACCNPQ::Engenharias::Engenharia de Produção